2011
DOI: 10.1249/mss.0b013e3181ef9d6b
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Immunity and Illness Incidence in Elite Rugby Union Players across a Season

Abstract: Regular monitoring of s-IgA and s-Lys may be useful in the assessment of exercise stress and URI risk status in elite team sport athletes. A combination of alterations in training intensity and seasonal influence is a likely contributor to observed peaks in URI incidence. It is probable that stress-induced increases in cortisol release contribute to reductions in mucosal immunity, which, when lowered, predispose rugby players to increased risk of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
100
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 31 publications
6
100
1
5
Order By: Relevance
“…Similar results were reported for male and female football players [34,45,55] but a tendency to decreased salivary flow rate and sIgA secretion rate was noted 3 days prior to the infection [34]; moreover, in the female athletes who later acquired URTI, a decreased concentration of sIgA was noted [45]. Also Cunniffe et al [11] found no relation between sIgA concentration and URTI incidence despite the fact that lowest sIgA concentration was noted in the month of highest URTI incidence and that URTI-affected athletes tended to have lower mean sIgA concentration compared with the healthy ones.…”
Section: Relationships Between Siga and Urtisupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results were reported for male and female football players [34,45,55] but a tendency to decreased salivary flow rate and sIgA secretion rate was noted 3 days prior to the infection [34]; moreover, in the female athletes who later acquired URTI, a decreased concentration of sIgA was noted [45]. Also Cunniffe et al [11] found no relation between sIgA concentration and URTI incidence despite the fact that lowest sIgA concentration was noted in the month of highest URTI incidence and that URTI-affected athletes tended to have lower mean sIgA concentration compared with the healthy ones.…”
Section: Relationships Between Siga and Urtisupporting
confidence: 80%
“…No unequivocal conclusions, however, could be drawn from those studies; for example, no significant relationship between URTI and total lysozyme concentration was found in rugby players [11], although the concentrations of lysozyme and of cortisol were negatively correlated. The authors speculated that the immunosuppressive function of cortisol might increase URTI risk [11].…”
Section: Relationships Between Siga and Urtimentioning
confidence: 90%
“…4,6 However, we currently cannot confirm a relationship between decreased sIgA responses and the occurrence of subsequent URS. We further found saliva flow rate to explain some of the variation observed in sIgA concentration on an intraindividual basis.…”
Section: Discussionmentioning
confidence: 76%
“…It plays an important role in mucosal immunity and has therefore been described as a first line of defense against pathogens and antigens presented at the mucosa, such as cold-causing viruses. 1,2 While a number of studies have found no relationships between upper respiratory symptoms (URS) and sIgA, 3,4 longer-lasting longitudinal studies have been able to associate preceding decreased resting levels of sIgA with URS. 5,6 Consequently, sIgA has been suggested to be a clinical biomarker to predict incidence of URS.…”
mentioning
confidence: 99%
“…Cunniffe et al 27 , investigating athletes from rugby during 11 months, and Neville et al 28 , monitoring yachtsmen for more than 50 weeks, found that psychological stress can increase the incidence of infections in athletes. In addition, Bishop and Gleeson 29 and Nakamura et al 30 confirmed that the number of URTI episodes tends to increase during competitive periods, corroborating the findings of the present study.…”
mentioning
confidence: 99%